'I thought I could get away from gender discrimination': linguistic instrumentalism and self-actualisation of female interpreters in temporary employment in Japan. Issue 4 (2nd October 2021) - Giustini, Deborah
Abstract: This article explores the narratives of a group of Japanese women who, to escape gender discrimination in regular employment, deploy their linguistic expertise in temporary employment as interpreters. Building on research that highlights women's investment dynamics into languages as an organising construct for their professional growth, this article argues that a category of Japanese women are increasingly turning to the 'foreign option' to mark their presence in the labour market for linguistic services as temporary workers, in a feminised industry where they feel gender equity is secured. Drawing upon in-depth interviews, this article uses the profession of interpreting as a key case for a micro-level ethnographic understanding of a temporary form of skilled linguistic work and women's aspirations. Adopting a critical approach to linguistic instrumentalism, it contributes to research by examining a small but ambitious segment of the Japanese female labour force, who – by mobilising rare communication skills – constructs an emancipatory turn from gender-stratified corporate structures. The study finds that interpreting, and the ethos of linguistic instrumentalism it carries, promises to informants a work–life balance and career growth. However, findings also show that informants' engagement with interpreting is not immune from gender stereotypes and occupational segregation, and thus remains a 'professional chimera'.